Pengaruh Varian Produk Dan Brand Image Terhadap Keputusan Pembelian Teh Pucuk Harum Di Kota Langsa - Nanang Waluyo; Suri Amilia; Muhammad Rizqi Zati (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to determine the effect of product variants and brand image on purchasing decisions of Pucuk Harum Tea in Langsa City. This study used a sample of 96 respondents who are consumers of Pucuk Harum Tea in Langsa City. Methods of data analysis using multiple linear regression equations, t test, F test and test the coefficient of determination. The results of this study show Y = 12.518 + 0.584X1 + 0.332X2. The results of the t test stated that product variants had a significant effect on purchasing decisions and brand image had a significant effect on purchasing decisions for Pucuk Harum Tea in Langsa City. The results of the F test stated that product variants and brand image had a significant effect on purchasing decisions for Pucuk Harum Tea in Langsa City. The results of the coefficient of determination test (Adjusted R2) obtained a value of 0.351 or 35.1% product variants and brand image can explain the purchase decision variable while the remaining 64.9% is influenced by other variables such as: cultural, social, personal, psychological factors and marketing mix .